The Effect of Staggered Shift Scheduling Mode on Nurses in the COVID-19 Isolation Ward- A Cross Sectional Study. (March 2021) - Lishan, Huang; Li, Tang; Lingna, Yu; Yuelin, Wu; Zixiang, Huang; Xiaobo, Tian
In order to explore the rational use of nursing resources in the epidemic situation of COVID-19, we optimized the shift arrangement in COVID-19 isolation area and constructed a reasonable nursing schedule under the condition of limited human resources. Seventy-eight nurses were arranged in COVID-19 isolation area to work for 1 week according to 3 different shifts: 4 + 4 h, 6 h and 6 h (overlapping by 1 h). Through the form of questionnaire, the comprehensive job satisfaction of 3 different models were compared, and the nursing quality and the consumption of protective equipment under 3 different modes were analyzed. The results showed that the comprehensive job satisfaction and nursing quality of nurses in 6 h (overlapping by 1 h) shift mode were better than those in other shift modes, and the consumption of protective equipment was lower.